Management of charcoal rot of cowpea using biocontrol agents and plant products - and KOUSALYA GANGADHARAN, C. USHAMALINI, K. RAJAPPAN (Indian Phytopathology, 2002)
The effect of biocontrol agents and plant products on Macrophomina phaseolina (causal agent of charcoal rot of cowpea) and other soil microorganisms, were studied. Soil application of neem cake at 150 kg/ha and farmyard manure at 10 t/ha reduced charcoal rot incidence significantly and increased crop yield. Both Trichoderma viride and T. harzianum recorded a root rot incidence of 17.0 and 17.6%, respectively, compared with 38.3% in the control. Seeds soaked in 10% leaf extracts of Adenocalymma alliaceum and Vitex negundo showed 98.4 and 97.8% germination compared with 92.3% in the control. Neem cake registered the maximum population of fungi, bacteria, actinomycetes and minimum population of M. phaseolina both in the rhizosphere and non-rhizosphere soil at the initial (20 DAS) and later (60 DAS) stages of crop growth. The rhizosphere population of T. viride in both stages of the crop was maximum in seeds treated with T. viride and in the non-rhizosphere region, neem cake and T. harzianum recorded the maximum population, respectively, at 20 and 60 DAS.